Development of pretreatment of empty fruit bunches for enhanced enzymatic saccharification - Rashid, Shah S,; Alam, Md Zahangir; Abdulkarim, Mohd Ismail; Mohd. Salleh, Hamzah (Academic Journals, 2011)
To achieve an accomplished optimized condition for enzymatic saccharification of palm oil mill empty fruit bunches (EFB) for higher yield of sugar hydrolysis, a comprehensive pretreatment of EFB was carried out using the laboratory produced cellulase enzyme through bioconversion of palm oil mill effluent (POME) by the fungal strain, Trichoderma reesei RUT C-30. This study was conducted by using two different types of agents (physical and chemical). Heating, boiling and steaming are among the physical agents and different concentrations of nitric acid, sulfuric acid and sodium hydroxide (NaOH) were the chemical agents used for the pretreatment of EFB to enhance the enzymatic saccharification of EFB. NaOH was proved to be the best among all the pretreatment agents and 3% NaOH was far higher and 2.35 fold increment was achieved on the yield of reducing sugar (175.03 mg/g of EFB) after 96 h of saccharification. A maximum of 41.82% yield of reducing sugar was achieved with 5% (w/v) of EFB and 7% (v/v) of enzyme after 120 h of saccharification when eight important parameters, namely saccharification duration, EFB size, EFB dose, enzyme dose, Tween 80, triton 100, agitation and incubation temperature, were examined in an OFAT (one factor at-a-time) design.